Intravital imaging reveals spatiotemporal dynamics of oncolytic Salmonella YB1-induced intratumoral vascular thrombosis and tumor targeting - Yu, Bin; Shi, Lei; Duan, Weiwang; Cui, Dongmei; Manuel, Edwin R.; Huang, Wei (Frontiers in Immunology, 2026)
IntroductionIn recent years, oncolytic bacterial therapy has emerged as a promising strategy in cancer research due to its unique advantages in tumor targeting and immune activation. Among various bacterial candidates, Salmonella demonstrates exceptional potential owing to its amenability to genetic engineering and its capacity to serve as an efficient vector for therapeutic gene delivery. However, the precise spatiotemporal dynamics of the interaction between Salmonella and tumor vasculature, as well as the mechanisms by which Salmonella targets and colonizes tumors via the circulatory system, remain to be fully elucidated.MethodsA dorsal skin-fold window chamber model was established in nude mice bearing tdTomato-labeled MDA-MB-231 xenografts. Real-time intravital imaging was used to track tumor growth, angiogenesis, and EGFP-labeled YB1 distribution after intravenous administration.ResultsFollowing intravenous injection, YB1 was retained in local vascular regions within the characteristically disordered tumor vascular network, such as "Shoulder Structure" or "Maze Structure". This physical entrapment facilitated direct interaction between YB1 and vascular endothelial cells, leading to endothelial damage and subsequent intratumoral vascular thrombosis. This process effectively blocked the tumor's blood supply and induced local hypoxia. Importantly, the formation of thrombosis and the hypoxic microenvironment further promoted the colonization and proliferation of YB1 within the tumor parenchyma, ultimately achieving effective tumor targeting and regression.DiscussionThis study reveals the novel mechanism of YB1's tumor targeting and colonization from the perspective of interaction with tumor vasculature. These findings providing critical theoretical support for the future design of more efficient and safer oncolytic bacterial therapies and lay a foundation for YB1’s clinical optimization.